Mengungkap Makna Spiritual Dan Budaya Dalam Simbol-Simbol Tradisi Maccera Manurung Di Enrekang - Sumai, Sumarni; A. Nurkidam; Fitrawan Rezky; Zulpiana Wahid (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
This study examines the spiritual and cultural meanings contained in the symbols of the Maccera Manurung ritual in Pasang Village, Enrekang Regency. Using Roland Barthes' semiotic approach, this study uncovers layers of denotative, connotative, and mythical meanings of various symbolic elements that appear in the ritual, such as Maddoa (giant swing), incense, Tau Tau (ancestral statues), and offerings. A qualitative approach with a case study design was applied to understand how the local community interprets the values ??of life and spirituality through these symbols. Data were collected through participant observation, in-depth interviews with traditional and community leaders, and documentation studies. The results show that the symbols in Maccera Manurung not only represent aspects of beliefs and traditions, but also strengthen the community's belief in the importance of balance between humans, nature, and the spiritual world as an effort to achieve protection, prosperity, and harmony. This study contributes to an understanding of the importance of preserving local cultural values ??that are rich in meaning and symbolic functions in community life.